2007
DOI: 10.1159/000108783
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Signaling Pathway Modulates the Airway Smooth Muscle Cell Phenotype in the Rat Model of Chronic Asthma

Abstract: Background: It has been demonstrated that the phenotypic modulation of airway smooth muscle cells (ASMCs) is important to the pathogenesis of airway remodeling in chronic asthma. The extracellular signal-regulated kinase 1/2 (ERK1/2) signaling pathway is one of the most important transduction pathways involved in the process of asthma; however, its role in the phenotypic transition of ASMCs remains unclear. Objectives: To examine the role of ERK1/2 in the phenotypic modulation of ASMCs in the rat model of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 82 publications
3
5
0
Order By: Relevance
“…42,43 Activation of ERK can promote the phosphorylation of cytosolic target proteins or regulate the activity of other protein kinases, promoting phosphorylation of multiple transcription factors and enhancing transcriptional activity. 44,45 In the present study, pravastatin significantly inhibited the increase in p-ERK1/2 expression in aortas from apoE −/− mice.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…42,43 Activation of ERK can promote the phosphorylation of cytosolic target proteins or regulate the activity of other protein kinases, promoting phosphorylation of multiple transcription factors and enhancing transcriptional activity. 44,45 In the present study, pravastatin significantly inhibited the increase in p-ERK1/2 expression in aortas from apoE −/− mice.…”
Section: Discussionsupporting
confidence: 57%
“…Many studies have demonstrated that in some cardiovascular diseases, such as atherosclerosis, ERK1/2 induces the phenotypic modulation of vascular cells during the progression of vessel remodelling . Activation of ERK can promote the phosphorylation of cytosolic target proteins or regulate the activity of other protein kinases, promoting phosphorylation of multiple transcription factors and enhancing transcriptional activity . In the present study, pravastatin significantly inhibited the increase in p‐ERK1/2 expression in aortas from apoE −/− mice.…”
Section: Discussionsupporting
confidence: 53%
“…29) Phosphorylated ERK1/2 moves from the cytoplasm across the nuclear membrane, activates associated proteins, induces Bcl-2-associated death promoter (BAD) phosphorylation, and activates a variety of nuclear transcription factors to play a role in anti-apoptosis. 30,31) In our experiments, TMP pretreatment increased the expression levels of p-Akt and p-ERK1/2 in H 2 O 2 -treated BMSCs. We speculated that TMP could modulate the activity of p-Akt and p-ERK1/2 to adjust the expression of apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 52%
“…Previous results have revealed that cigarette smoke exerts its biological effects via the ERK1/2 signaling pathway ( 8 ). Moreover, a critical role for ERK1/2 activation in the abnormal proliferation of vascular smooth muscle cells and airway smooth muscle cells has been suggested during vessel remodeling ( 11 14 ). The present study extended this finding and demonstrated that the expression of p-ERK1/2 was upregulated by CSE stimulation, indicating that activated ERK1/2 is involved in the CSE-induced proliferation of primary rPASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK1/2 (p-ERK1/2) has been implicated as a regulator in numerous fundamental cellular activities ( 9 , 10 ). Studies by the current authors and other researchers have addressed the role of the ERK1/2 signaling pathway in the proliferation of airway smooth muscle cells and multiple arterial smooth muscle cells ( 11 14 ).…”
Section: Introductionmentioning
confidence: 99%